Обґрунтування структури та параметрів бронекорпусів легкоброньованих машин за критеріями захищеності шляхом комп'ютерного моделювання процесів і станів при дії засобів ураження - Васильєв, Антон Юрійович; Танченко, Андрій Юрійович; Ткачук, Микола Миколайович; Скріпченко, Наталія Борисівна; Лісовол, Яна Миколаївна (НТУ "ХПІ", 2016)
В роботі наведено порівняння кількох військових броньованих машин різного типу. Наведено огляд найбільш використовуваних шляхів підвищення рівня захищеності. Запропоновано новий підхід до оцінки рівня захищеності шляхом інтегрованого аналізу найбільш поширених засобів ураження, за низкою вхідних параметрів бронекорпусів та вихідних критеріїв. Наведено деякі результати числового моделювання під час дії ударних хвиль від потужних вибухів на корпус броньованих машин та результати оцінки корпусів легкоброньованих машин на можливість пробиття стрілецькою зброєю.

The article provides a comparison of the different types military armored vehicles numbers. A most used ways to increase the protection level of armored vehicles are reviewed. A new approach to the estimation of the armored vehicles protection level by means of integrated computer-aided analysis of the most common destruction means, with a number of input vehicles body parameters and output criteria. The results of numerical simulation of the explosion shock waves action on armored vehicles body, and simulation of the possibility to penetrate of light armored vehicles bodies by infantry riffle ammunition. Stress-strain state obtained as a result of explosion simulation give information about deformation, plastic strain of armored plates and structure elements of armored vehicles body. Stress-strain state obtained with help of finite element method. Analysis of penetration danger level / protection level can be performed with the shooter point of view, for understanding where making the shot. Also analysis of penetration can be performed for understanding how areas around the armored vehicles separate with the level of danger / protection for vehicle. Calculation of penetration process are performed with methods which are developed by authors.
The definition of structure and parameters of light-armored vehicle body FOR maximising its protection criteria by computer-aided modelling of processes and reactions during different ways of its defeat
Keywords: тактико-технічна характеристика; напружено-деформований стан; метод скінченних елементів; НДС; stress-strain state; finite element method